TINJAUAN ETIKA BISNIS ISLAM TERHADAP ASPEK PEMASARAN - Budi Sufyanto; Zainol Hasan (Al-Idarah, 2021)
The purpose of this paper is to examine the marketing aspects in the perspective of Islamic business ethics according to Islamic economists. This writing is a literature research with a qualitative descriptive approach. The data source is a reference according to the topic of study. Data analysis was carried out qualitatively including data reduction, data presentation and conclusion drawing. The results showed that the aspects of Islamic marketing were minimal and more dominant over conventional marketing